2016
DOI: 10.1002/2016jd024749
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of water vapor and energy exchanges above two contrasting Sudanian climate ecosystems in Northern Benin (West Africa)

Abstract: Natural ecosystems in sub‐Saharan Africa are experiencing intense changes that will probably modify land surface feedbacks and consequently the regional climate. In this study, we have analyzed water vapor (QLE) and sensible heat (QH) fluxes over a woodland (Bellefoungou, BE) and a cultivated area (Nalohou, NA) in the Sudanian climate of Northern Benin, using 2 years (from July 2008 to June 2010) of eddy covariance measurements. The evaporative fraction (EF) response to environmental and surface variables was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 86 publications
0
17
6
Order By: Relevance
“…The observed Ω was lower than those reported by Mamadou et al (2016) who observed values ranging from 0.05-0.45 during the dry and wet season, respectively, in northern Benin. The observed Ω was lower than those reported by Mamadou et al (2016) who observed values ranging from 0.05-0.45 during the dry and wet season, respectively, in northern Benin.…”
Section: Biophysical Controls Of Energy Partitioningcontrasting
confidence: 88%
See 1 more Smart Citation
“…The observed Ω was lower than those reported by Mamadou et al (2016) who observed values ranging from 0.05-0.45 during the dry and wet season, respectively, in northern Benin. The observed Ω was lower than those reported by Mamadou et al (2016) who observed values ranging from 0.05-0.45 during the dry and wet season, respectively, in northern Benin.…”
Section: Biophysical Controls Of Energy Partitioningcontrasting
confidence: 88%
“…The low Ω observed suggests that ET was largely controlled by VPD and G s , and the canopy was strongly coupled with the boundary layer. The observed Ω was lower than those reported by Mamadou et al (2016) who observed values ranging from 0.05-0.45 during the dry and wet season, respectively, in northern Benin.…”
Section: Biophysical Controls Of Energy Partitioningcontrasting
confidence: 88%
“…The sensible and latent energy fluxes from the fallow were lower than those of the forest in 2010, whereas when short season millet was growing, they were more similar. By comparing the changes in soil moisture along the diurnal cycle, we see that even in the dry season there is some variation, particularly at shallow depths; thus, in contrast to other authors, we cannot attribute the early peak purely to stomata behavior during the dry season (Mamadou et al, 2016). In contrast, during the rainy season, it declined, following the cycle of available radiation.…”
Section: Energy Balancecontrasting
confidence: 71%
“…These values are in general higher than previously found in similar environments during the rainy season (Bagayoko et al, 2007;Brümmer et al, 2008;Guyot et al, 2012;Mamadou et al, 2016). In contrast, our site has a lower dry season evaporative fraction than nearby sites, which suggests that moisture cycling during the wet season is more complete and that there is less storage into the dry season.…”
Section: Evaporative Fractioncontrasting
confidence: 64%
See 1 more Smart Citation